Kinesioterapia respiratoria como tratamiento en el paciente pediátrico. - Pérez León, María Auxiliadora (2024)
Pneumonia is an infection of the lungs, which causes the air sacs to fill with pus and other fluids, while asthma is a disease that causes inflammation and narrowing of the airways. In both diseases until now the treatment has consisted only in the prescription of medication (mainly bronchodilators and anti-inflammatory drugs), but scientific evidence has shown that the use of respiratory kinesiotherapy has achieved the improvement of symptoms as well as slowing the progression of the disease in this population. The objective of the research project is to list the techniques of respiratory kinesiotherapy applied in the treatment of respiratory diseases in pediatric patients for this purpose, a bibliographic search was carried out in the databases PubMed, Scielo, Cochrane, Dialnet, using descriptors or keywords as well as the use of Boolean operators establishing the following search equation: [(“asthma”) (“pneumonia”) and (“physiotherapy”) and (“child” OR “teen”)], where 120 articles were selected that met the inclusion criteria, most of them used physical exercise as a form of treatment demonstrating its efficacy in different parameters, as well as other therapies such as The Buteyko Method, Papworth Method, prolonged slow expiration with open glottis, assisted autogenous drainage, prolonged slow expiration, assisted cough, use of instruments such as Acapela, and Therape, where after filtering and analysis, 25 articles related to respiratory kinesiotherapy and pediatric respiratory diseases such as asthma and pneumonia were selected to structure this research work. The research concluded that physical therapy has proven to be a safe and effective discipline in the treatment of children with respiratory problems, such as asthma and pneumonia. Specifically, the use of respiratory kinesiotherapy provides a significant improvement in the control of symptoms, which allows the child to have a better quality of life, but there is still controversy regarding its possible favorable effects due to the scarcity of clinical trials and heterogeneity of results in this population.